Effect of Financial Performance of Jordanian Islamic Banks In the Amman Stock Exchange for the period (1990-2008) - عبد, حميد عبيد; الموسوي, حيدر يونس (Journal of Economics and Administrative Sciences, 2011)
The last four decades have witnessed a number of rapid and successive international changes in terms of future impacts and orientations. International economy has transformed into a competitive small village due to the information technology revolution and the liberation processes and the economic openness that the market witnesses, there became one market and the activists in this international market are not governments only but rather international organizations and huge multinational corporations where each spares no effort to take every opportunity and face challenges within the frame of  removing all impediments and release transactions under the auspices of  these global developments, the idea of creating Islamic banks was accelerated  for this topic is regarded a new subject within the financial and banking sciences. Albeit the challenges that impede the Islamic financial transactions are immense, these organizations managed to anchor its bases and build a steadfast base as regards international financial transactions. Islamic banks became a reality in the world of international financial life after they nosed their way in banking domains quite remote from their Islamic bases and mechanisms. These banks have also managed to score tangible successes through offering a group of very distinguished financing formulae far from the rule of usury and debts on which the traditional  banking systems rely.The significance of this study lies in assessing  Islamic banks as holding a very important position in the Islamic world for it can be considered as a theoretical frame and a scientific subject in the financial and banking science by means of  expanding the area of treatments and the transformation from the theoretical to the applied aspect. The significance of the study emanates also from showing the impact of Islamic banks through their financial performance in the indexes of the financial markets and then getting to know the scope of their influence the international financial markets exchange in a sample of countries. The problem of the study is represented in the fact that though four decades have passed since Islamic banks were established  and the huge amounts of money invested, the impact of these banks on the international markets exchange has not been tested because there is an uncertainty characteristic of  the relationship between these banks and the international markets exchange which is ascribable to the fact that these banks do not deal in the same financial instruments that abide by the interest principle on which the markets exchange is based.